Association of the Geriatric Nutritional Risk Index with incident hypertension in the older Chinese population: a 6-year cohort study. Issue 5 (May 2021) - Su, Zhongjian; Zhang, Xing; Zheng, Nan; Xiao, Ying; Liu, Xingzhu; Yang, Yanfei; Deng, Lili; Chen, Yanfei; Li, Bin
Background: We examined the association of the Geriatric Nutritional Risk Index (GNRI) with the incidence of hypertension. Methods: We used data of the China Health and Nutrition Survey in this study. Participants aged ≥60 years were eligible. The GNRI was defined as follows: GNRI = [1.489 × albumin (ALB; g/L)] + [41.7 × (actual weight/ideal weight)]. Participants with systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥90 mmHg, or use of antihypertensive medication were defined as having hypertension. Results: This study included 4853 participants, comprising 3612 control participants and 1241 participants with hypertension. The GNRI, ALB, and body mass index (BMI) were significantly associated with higher incidence of hypertension (HR: 1.030, 1.026, and 1.088; 95% CI: 1.020–1.041, 1.008–1.044, and 1.069–1.107, respectively). The GNRI, ALB, and BMI were associated with an earlier age of hypertension onset (β = −0.403, −0.613, and −0.321; 95% CI: −0.493 to −0.314, −0.767 to −0.459, and −0.484 to −0.159, respectively). Conclusions: A higher GNRI was associated with increased incidence of hypertension. An elevated GNRI was associated with earlier age of hypertension onset.